2007
DOI: 10.1042/bst0350421
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis signalling pathways in seizure-induced neuronal death and epilepsy

Abstract: Delineating the molecular pathways underlying seizure-induced neuronal death may yield novel strategies for brain protection against prolonged or repetitive seizures. Glutamate-mediated excitotoxicity and necrosis is a primary contributing mechanism but seizures also activate programmed (apoptotic) cell death pathways. Apoptosis signalling pathways are typically initiated following perturbation of intracellular organelle function (intrinsic pathway) or by activated cell-surface-expressed death receptors (extri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…35) Glutamate receptor antagonists protect against seizure damage, but their therapeutic value is unlikely to be realized because of neurotoxic side effects, particularly in the young, and the profound disturbance these drugs impart on normal brain function. 36) Accordingly, alternative approaches to targeting seizure-induced neuronal death are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35) Glutamate receptor antagonists protect against seizure damage, but their therapeutic value is unlikely to be realized because of neurotoxic side effects, particularly in the young, and the profound disturbance these drugs impart on normal brain function. 36) Accordingly, alternative approaches to targeting seizure-induced neuronal death are required.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis may be triggered by two main pathways: activation of cell surfaceexpressed death receptors of the tumor necrosis factor TNF, superfamily and disruption to intracellular organelle homeostasis or DNA damage. 35) Seizure-induced mitochondrial dysfunction and activation of Bcl-2 family are calcium dependent or at least partly of calcium dependent, 38,39) whereas a role for death receptors contributing to seizure-induced neuronal death is less likely because there is no apparent requirement for calcium in the activation mechanism. 35,40) Our results suggest that the neuroprotective effect of PIP should be calcium dependent and participate in protecting intracellular organelles, such as mitochondrion and endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that seizures can activate the intrinsic and extrinsic apoptotic pathways in the brain (Henshall, 2007). The release of cytochrome c, Apaf-1, activated caspase-9 and -3 and subsequent DNA fragmentation in the rat hippocampus after a short SE duration indicate activation of the intrinsic pathway (Turski et al, 1983;Leite et al, 1990).…”
Section: Seizures Activate Apoptosismentioning
confidence: 99%
“…This ultimately culminates with cell necrosis (Fujikawa, 2005(Fujikawa, , 2006. The glutamate-mediated excitotoxicity and necrosis are primary contributing factors, but seizures also activate programmed cell death pathways, such as apoptosis (Henshall 2007(Henshall , 2008.…”
Section: Cell Death Secondary To Seizuresmentioning
confidence: 99%
See 1 more Smart Citation